2015
DOI: 10.1016/j.jsps.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo targeting effect of folate decorated paclitaxel loaded PLA–TPGS nanoparticles

Abstract: Paclitaxel is one of the most effective chemotherapeutic agents for treating various types of cancer. However, the clinical application of paclitaxel in cancer treatment is considerably limited due to its poor water solubility and low therapeutic index. Thus, it requires an urgent solution to improve therapeutic efficacy of paclitaxel. In this study, folate decorated paclitaxel loaded PLA-TPGS nanoparticles were prepared by a modified emulsification/solvent evaporation method. The obtained nanoparticles were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Previous studies using similar nanoparticles showed that PTX-loaded copolymer PLA-TPGS-induced apoptosis in HepG2 cells [26]. In addition, folate decorated PTXloaded PLA-TPGS nanoparticles are more effective targeting at cancer cells both in vitro and in vivo than PTX alone [27]. A recent study demonstrated that TiO 2 , SiO 2 , and hydroxyapatite nanoparticles could strengthen intracellular tension and retard cellular migration [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using similar nanoparticles showed that PTX-loaded copolymer PLA-TPGS-induced apoptosis in HepG2 cells [26]. In addition, folate decorated PTXloaded PLA-TPGS nanoparticles are more effective targeting at cancer cells both in vitro and in vivo than PTX alone [27]. A recent study demonstrated that TiO 2 , SiO 2 , and hydroxyapatite nanoparticles could strengthen intracellular tension and retard cellular migration [28].…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel is one of the most effective chemotherapeutic agents but it has poor water solubility and low therapeutic index so it needs an urgent solution to increase therapeutic efficacy of paclitaxel. According to this subject, in 2015, Thu et al [78] Figure 10). Barba group synthesized new nanovectors based on copolymer of α, β-poly(N-2-hydroxyethyl)-D,L-aspartamide (PHEA) and PLA to control release of lipophilic drugs [80].…”
Section: Application Of Biodegradable Nanostructure Polymersmentioning
confidence: 98%
“…Vinyl Prolidon Poly -Chloride Stearoin -Chitosan [7]; PEG-Folic Acid [8]; Chitosanoligosaccharides-Au [9]; and Folate -PLA-TPGS [10]. Recently, there are no research have reported cellulose of cassava baggase as delivery of paclitaxel.…”
Section: Certain Polymers Have Been Used As Paclitaxel Delivery Includementioning
confidence: 99%
“…Induction of paclitaxel against cancer cells also causes apoptosis; cell fatality is mediated by caspase (one of cysteine protease). Morphologically, during apoptosis occurs chromatics condensation [9][10]. In the leukemia, paclitaxel induce caspase so causes cell death in the range of 16-36 hours [16].…”
Section: Mechanism Of Paclitaxel Kill Cancermentioning
confidence: 99%